Satisfacción sexual: revisión de los factores individuales y de pareja relacionados - Ahumada G, Sandra; Lüttges D., Carolina; Molina G., Temistocles; Torres G., Soledad (Revista Hospital Clínico Universidad de Chile, 2014)
Sexual satisfaction, understood as a subjective assessment of liking or disliking a person makes regarding their sexual life, is now considered a key factor of sexual health and an important indicator for health and quality of life, according to WHO guidelines. Therefore, this issue has become increasingly relevant in the studies on sexuality and health. However, the information available in Chile and Latin America is limited, suggesting the need to generate studies to have updated knowledge regarding to chilean reality